EFFECT OF LOW PH ON ELECTROLYTES EVALUATION OF OREOCHROMIS MOSSAMBICUS - D, Kumar; M, Narayanan; A, Ibrahim (Malaysian Journal of Science, 2004)
The fish Oreochromis mossambicus was selected for this present investigation. O. mossambicus were exposed to different degrees of acid exposures such as, pH 4.9, 5.8 and control and they were fed with beef meat. The objective of this present study was to quantify the electrolytes (Na, K, CI and Ca) present in the serum of the blood of acid stressed O. mossambicus. Results obtained in the present investigation clearly indicated that the electrolytes drastically decreased from the control and led to circulatory collapse. The results exhibited the reduction of Na from the control and led to circulatory collapse. The results exhibited the reduction of Na from the control 17.93mmol/l in pH 4.9. Similarly and pH 5.8 the reduction of Na + was 9.6 mmol/l from the control. Similarly the reduction of chloride and potassium were 103./1 mmol/l, 112.53 mmol/l, 130.1 mmol/l, respectively, Calcium also reduced from the control 1.9mg/mmol/l respectively, and 567 in the fishes exposed to pH 4.9 and 5.8 respectively.